2018
DOI: 10.1093/abm/kax048
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Invitations Using the Question-Behavior Effect and Financial Incentives to Promote Health Check Uptake in Primary Care

Abstract: Background Uptake of health checks for cardiovascular risk assessment in primary care in England is lower than anticipated. The question-behavior effect (QBE) may offer a simple, scalable intervention to increase health check uptake. Purpose The present study aimed to evaluate the effectiveness of enhanced invitation methods employing the QBE, with or without a financial incentive to return the questionnaire, at increasing uptake of health checks. Methods We conducted a three-arm randomized trial including all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Uptake in the intervention arm was 33.5% compared to 29.3% in the control arm, an absolute difference of 4.2% and a relative difference of 14.3% in NHSHC attendance. However, McDermott and colleagues [25] found that mailing patients a Question-Behaviour Effect questionnaire (with or without an incentive for returning the questionnaire) 1 week before invitation letters did not significantly improve uptake in the intervention groups compared to the control group. These researchers found that uptake was higher for intervention group individuals who returned the questionnaire, but when examining the intervention group as a whole (i.e., in an intention to treat analysis), there was no significant effect of including a questionnaire (p = .070) or a questionnaire plus incentive (p = .054) compared to controls.…”
Section: Interventions On Invitation Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…Uptake in the intervention arm was 33.5% compared to 29.3% in the control arm, an absolute difference of 4.2% and a relative difference of 14.3% in NHSHC attendance. However, McDermott and colleagues [25] found that mailing patients a Question-Behaviour Effect questionnaire (with or without an incentive for returning the questionnaire) 1 week before invitation letters did not significantly improve uptake in the intervention groups compared to the control group. These researchers found that uptake was higher for intervention group individuals who returned the questionnaire, but when examining the intervention group as a whole (i.e., in an intention to treat analysis), there was no significant effect of including a questionnaire (p = .070) or a questionnaire plus incentive (p = .054) compared to controls.…”
Section: Interventions On Invitation Methodsmentioning
confidence: 94%
“…The length of studies (including the follow up period) varied from 6 months [23] to 4 years [22]. Six studies achieved a strong quality assessment rating [9,20,21,[23][24][25] and three achieved a moderate rating [19,22,26]. There were only two randomised controlled trials identified [21,25], with the remaining studies consisting of one observational cohort [9] and six cross sectional studies [19,20,[22][23][24]26].…”
Section: Study Characteristics and Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations